2021
DOI: 10.1002/prot.26078
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanisms of light‐oxygen‐voltage domain color tuning from a set of high‐resolution X‐ray structures

Abstract: Light‐oxygen‐voltage (LOV) domains are widespread photosensory modules that can be used in fluorescence microscopy, optogenetics and controlled production of reactive oxygen species. All of the currently known LOV domains have absorption maxima in the range of ~440 to ~450 nm, and it is not clear whether they can be shifted significantly using mutations. Here, we have generated a panel of LOV domain variants by mutating the key chromophore‐proximal glutamine aminoacid of a thermostable flavin based fluorescent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…Therefore, we conclude that irrespective of the buffer and post-translational modification, the C terminus of the iLOV-Q489K and CagFbFP-Q148K variants is unlatched, the LOV core domain is opened up to allow solvent ingress, and the introduced lysine occupies an extended conformation facing away from the FMN chromophore. The related variant CagFbFP-Q148R, which was recently reported, also shows blue-shifted spectral properties, featuring an unlatched C terminus (26). We thus suggest these structural changes as the characteristic features for a blue-shifted absorption and emission spectrum, that is, when compared with the parental FbFPs.…”
Section: Resultssupporting
confidence: 62%
“…Therefore, we conclude that irrespective of the buffer and post-translational modification, the C terminus of the iLOV-Q489K and CagFbFP-Q148K variants is unlatched, the LOV core domain is opened up to allow solvent ingress, and the introduced lysine occupies an extended conformation facing away from the FMN chromophore. The related variant CagFbFP-Q148R, which was recently reported, also shows blue-shifted spectral properties, featuring an unlatched C terminus (26). We thus suggest these structural changes as the characteristic features for a blue-shifted absorption and emission spectrum, that is, when compared with the parental FbFPs.…”
Section: Resultssupporting
confidence: 62%
“…In prolinesubstituted CagFbFP variants, the temperature of both transitions is raised by up to ~ 2°C [31]. In the variants generated to achieve spectral tuning, both transitions are shifted to lower temperatures [32,33]. Finally, two or even three different transitions were observed in variants with extended flexible loops of different lengths, which were designed for identification of the best potential split sites during the process of generating a split flavin-based fluorescent reported based on CagFbFP [34].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies recently also provided a molecular characterization of the spectral effects of mutations on iLOV to gain a mechanistic understanding. Röllen and colleagues have shown that iLOV V392T/Q489K fluorescence has a slight red-shift with an emission spectrum maximum of 502 nm . Similar mutations on iLOV homolog protein CagFbFP I52T/Q148K with the emission maximum of 504 nm and another blue-shifted variant CagFbFP Q148K with the emission maximum of 491 nm were used in fluorescence microscopy experiments and were successfully spectrally separated .…”
Section: Discussionmentioning
confidence: 99%